Successfully treatment of PLZF-RARα positive acute promyelocytic leukemia by Venetoclax combining with decitabine: a case report and literature review - Ziwei Zhou; Erling Chen; Jiqian Jiang; Lei Xue; Lijun Zhu; Xing Hu; Yingqiao Zhu; Changcheng Zheng; Juan Tong (Hematology)
Introduction: Acute promyelocytic leukemia (APL) is mainly due to the chromosome translocation t(15; 17) (q22; q12), leading to the formation of PML-RARα fusion protein. However, some patients carried rare translocation involving RARα gene, and they were referred to as variant APL caused by the RAR family (RARα, RARB, and RARG) and partner genes. PLZF-RARα was a rare type of molecular genetic abnormality with unfavorable prognosis that has been reported in few cases in variant APL. Knowledge of PLZF-RARα (+) APL treatment remains limited understood.Case report: We presented a case of variant APL in a 47-year-old female, who was PLZF-RARα positive detected by reverse transcription polymerase chain reaction (RT–PCR). The patient did not respond to all-trans retinoic acid (ATRA), idarubicin, and arsenic trioxide (As2O3) combined induction chemotherapy. Then, the patient was treated with Venetoclax combining with decitabine as the salvage therapy and achieved morphological remission and PLZF/RARα gene negative.Conclusion: Venetoclax combining with decitabine can be used as an effective therapy in the PLZF-RARα positive APL.